(untitled) (Indian Journal of Arid Horticulture, 2025)
In India wild groves of seedling date palms are found on the coastal beft from Anjar to Mandvi in Kachergtjchh district of Gujarat and these groves are believed to be 200 years old. A great diversity is existing in morphological character- istics of indigenous date palms of Kachchh, hence molecular characterization of this precious genetic resource is significant. Improvement of date palm through conventional breeding methods is very difficult due to its long life cycle, strongly heterogeneous nature and impossibility to determine the sex at early stages of development. Marker assisted selection based on molecular characterization can overcome these hurdles. The study was done at Date palm Research Station, Mundra and C.P. College of Agriculture, Sardarkrushinagar, Gujarat. RAPD fingerprints were performed on DNA extracted from 10 elite date palm germplasm. The analysis had two objectives to detect polymorphism within cultivars of date palm and to investigate the genetic diversity of the indigenous date palm germplasm of Kachchh. Out of eight random primers screened, two primers OPD 16 and OPD 20 produced comparatively good polymorphic bands. The efficiency of RAPD as a simple molecular marker for cultivar identification and genetic relationships among different date palm germplasm are discussed.